The health consequences of migration: Meeting the health needs of displaced populations - Brijnath, Bianca; Browne, J.; Halliday, J.; Renzaho, A. (2011)
The present scale of migration raises a number of public health challenges. In this paper, the health consequences of migration are examined among forced migrants (internally displaced people and refugees) and voluntary migrants. Alongside we also focus on the health needs of migrants in developed and developing nations. Theory and evidence are linked to document existing needs and access to health services. We argue that public health has a role to play in building social inclusiveness and equity, and make recommendations about how this process of inclusion can be facilitated.